Somatic Landscape of Oncogenic Variants Across the Main Cancer Subtypes in Latin America: A Narrative Review - Talia Wegman-Ostrosky; Lucia Taja-Chayeb; Zyanya Lucia Zatarain-Barrón; Catalina Trejo-Becerril; Daniela Shveid Gerson; Isabel Espino-Gutiérrez; Andrea Gutiérrez-Lara; Andrés Yesid Bonilla Salcedo; Mistral Castellanos Mares; José Elias García-Ortiz; Carla Daniela Robles-Espinoza; Alejandro Ruíz-Patiño (JCO Global Oncology)
Variations in somatic genetic alterations can be observed across different cancer types and diverse populations. Understanding the frequency of oncogenic variants in specific populations helps elucidate carcinogenesis and risk factors, with somatic variants often serving as treatment markers. Data regarding the somatic landscape across the main tumor subtypes in patients from Latin America and the Caribbean (LAC) have increased recently, highlighting important differences from contrasting populations in North America, Europe, and Asia. Many of these differences have pressing implications regarding screening, risk factor management, targeted therapies, and health care policy. This review aims to synthesize the existing information on somatic oncogenic variants in patients' tumors from LAC. We included the frequency of somatic oncogenic variants of the most frequent tumors in LAC: prostate cancer, female breast cancer, colon cancer, gastric cancer, and lung cancer. Furthermore, we add information from tumors that are relevant in LAC because of their high incidence, specific subtypes, or aggressive phenotypes, namely gallbladder cancer, acral melanoma, and hematologic neoplasms, respectively. The data highlight distinct differences in the reported prevalences of various somatic variants across a spectrum of neoplasms. Moreover, it demonstrates that an extensive number of genetic and molecular studies have been carried out in the region, improving the level of characterization for this complex, admixed population. Nonetheless, data from many individual countries are still scarce or altogether missing, underscoring the need to establish collaborative groups to further advance progress in LAC. The need for further comprehensive research in the area should not be substituted with data from other regions as we seek to empower the choices to improve our health care outlook.